Determinants of perceived usefulness of e-learning systems. (November 2016) - Alsabawy, Ahmed Younis; Cater-Steel, Aileen; Soar, Jeffrey
Abstract: E-learning systems are increasingly essential in universities, schools, government departments and other organizations that provide an education or training service. The objective for adopting e-learning systems is to provide students with educational services via electronic channels. The focus of this study is on the impact of IT infrastructure services and IT quality on perceptions of usefulness of e-learning systems. A model is proposed which includes five constructs: IT infrastructure services, system quality, information quality, service delivery quality, and perceived usefulness. A quantitative study was conducted at an Australian university with 720 survey responses from students who were enrolled in online courses. The results suggest that IT infrastructure services play a critical role in generating information with high quality, enhancing the aspects of e-learning system quality, and improving service delivery quality. The impact of IT infrastructure services, system quality, and information quality on perceived usefulness is fully mediated by service delivery quality. Universities need to be aware of the critical impact of IT infrastructure services and consider how investment in these services could improve system and information quality, service delivery quality, and the usefulness and success of e-learning systems. Highlights: A survey is used to examine the determinants of perceived usefulness of e-learning systems. The impact of IT Infrastructure and IT Quality on Perceived Usefulness is tested. The role of service delivery quality as a mediating factor is investigated. IT Infrastructure and Quality as determinants of Perceived Usefulness are confirmed. Service quality was a significant mediating factor to achieve perceived usefulness.